An advanced modulation scheme emphasising neutral point ripple suppression using predictive control for three-level NPC converters in aircraft electric starter generator applications - Li, Chen; Yang, Tao; Lo Calzo, Giovanni; Bozhko, Serhiy; Gerada, Chris; Wheeler, Patrick (2018)
Electrical starter/generator (ESG) system is one of the key innovations of more-electric aircraft initiative. The ESG cranks the engine and accelerates it up to self-sustained speed using electric energy (starter mode) and then runs as a generator to supply onboard loads. Three-level neutral point clamped (NPC) converter have been identified as a preferable choice for ESG applications due to high power quality as well as efficiency. However, the application of three-level NPC converter in the ESG systems has certain challenges. One of which is the low frequency neutral point voltage ripple, especially in generation mode when running at high speeds such that the flux weakening control is required. The paper proposes an advanced modulation scheme which can balance the neutral point voltage for the full range of speeds and loading conditions. Using the proposed technique, zero neutral point voltage deviation within each switching period is achieved by introducing a sharing factor computed in a deadbeat predictive approach. The proposed technique is validated with simulation results.